(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Cellular system adopts the idea of frequency reuse, where the frequency bandwidth of each cell is repeated in non-adjacent cell, in order to use the available frequency band efficiently, however, the interference occurs even between the distant cells. The aim of the paper is to reduce the interference between these co-cells. The user receives the signal from its own cell, as well as the signal from the far cell which has the same frequency, the parameter Signal to Interference Ration, SIR, is the main factor to evaluate the performance of the cellular system. In this paper, we propose algorithm to move the locations of base stations of the cells, in order to increase SIR value, decrease Probability of blocking, and number of users out of coverage.